2021
DOI: 10.3390/jcm10184119
|View full text |Cite
|
Sign up to set email alerts
|

Management of Spontaneous Bleeding in COVID-19 Inpatients: Is Embolization Always Needed?

Abstract: Background: critically ill patients with SARS-CoV-2 infection present a hypercoagulable condition. Anticoagulant therapy is currently recommended to reduce thrombotic risk, leading to potentially severe complications like spontaneous bleeding (SB). Percutaneous transcatheter arterial embolization (PTAE) can be life-saving in critical patients, in addition to medical therapy. We report a major COVID-19 Italian Research Hospital experience during the pandemic, with particular focus on indications and technique o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The COVID-19-specific incidence of spontaneous muscular hematoma is actually unclear; Riu et al reported an incidence of 1.95% of soft-tissue spontaneous bleeding [ 20 ], higher than observed in general hospitalized patients receiving low-molecular-weight heparin (LMWH) for some reason. An explanation could be found in the physiopathology of SARS-CoV-2 infection related to endothelial damage [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The COVID-19-specific incidence of spontaneous muscular hematoma is actually unclear; Riu et al reported an incidence of 1.95% of soft-tissue spontaneous bleeding [ 20 ], higher than observed in general hospitalized patients receiving low-molecular-weight heparin (LMWH) for some reason. An explanation could be found in the physiopathology of SARS-CoV-2 infection related to endothelial damage [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection carries a special condition of endotheliitis both for the viral infection of the cell and for the inflammatory response with subsequent cytokine storm, with the consequence of micro and macro thrombosis, as well as endothelial injury leading to micro-vessel fragility [ 20 ]. Endothelial damage was the reason why hospitalized patients were advised to treat hospitalized patients with high doses of LMWH (especially in the first wave, preventive doses are currently preferred), and why it is also difficult to achieve hemostasis in case of bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations